(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
A positive image is very necessary for a company to promote its values and be accepted in society. However, if the positive image narrated is contrary to reality, then the case can be categorized as green-washing, if it concerns the environment, and woke-washing, if it concerns social welfare. Furthermore, literary works as a mirror of society have room to represent green-washing and woke-washing, one of which is in the novel How Beautiful We Were by Mbue. In the novel, green-washing and woke-washing are not just image manipulation for profit but also play a major role in perpetuating eco-apartheid by the American oil company called Pexton which occurred in the village of Kosawa. Based on this case, this research aimed to rigorously analyze the extent of eco-apartheid inflicted upon the affected community. Furthermore, it also attempt to critically uncover the mechanism that not only mask corporate exploitation but also actively reinforce eco-apartheid. Moreover, to achieve this goal, this research uses descriptive qualitative and the concept of levels of marginalization of eco-apartheid, green-washing, and woke-washing. This study used close reading to systematically identify words, phrases, and sentences that revealed different levels of eco-apartheid, green-washing, and woke-washing. The collected data was then analyzed to uncover the extent and deeper mechanisms that allow eco-apartheid to persist based on the theories used. This research finds that the level of marginalization in eco-apartheid has reached the third level. Then, eco-apartheid is maintained through a green-washing mechanism, namely by creating the illusion of concern for environmental pollution and clean water, and a woke-washing mechanism, namely by promoting Pexton’s concern for social welfare, offering job opportunities, compensation money and scholarships.